PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT AMARILYS ROYAL TAMA TANGERANG SELATAN - Roy, Muhammad; Apriansyah, Muger (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of compensation and work motivation on employee productivity at PT Amarilys Royal Tama. The study employs a quantitative method with a causal associative approach. The sampling technique used is saturation sampling, and a total of 60 respondents were obtained for this study. Data analysis involves validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of this study indicate that (1) Compensation has a positive and significant effect on employee productivity with the regression equation Y= 11.566 + 0.720X1, with a correlation value of 0.637, meaning both variables have a strong relationship. The coefficient of determination is 40.6%. The hypothesis test yielded a t-value of 3.374 > 2.002 (t-table) and a significance value of 0.001 < 0.05. Thus, H0 is rejected, and Ha1 is accepted, indicating a positive and significant influence of compensation on employee productivity. (2) Work motivation has a positive and significant effect on employee productivity with the regression equation Y= 7.778 + 0.735X2, with a correlation value of 0.617, indicating a strong relationship between the two variables. The coefficient of determination is 38.0%. The hypothesis test yielded a t-value of 2.926 > t-table 2.002 and a significance value of 0.005 < 0.05. Thus, H0 is rejected, and Ha2 is accepted, indicating a positive and significant influence of work motivation on employee productivity. (3) Compensation and work motivation have a positive and significant influence on employee productivity with the regression equation Y= 3.542 + 0.466X1 + 0.426X2, with a correlation coefficient of 0.695, indicating a strong relationship between the independent and dependent variables. The coefficient of determination is 48.3%, while the remaining 51.7% is influenced by other factors. The hypothesis test yielded an F-value of 26.662 > 3.16 (F-table) and a significance value of 0.000 < 0.05. Therefore, H0 is rejected, and Ha3 is accepted, indicating a positive and significant simultaneous influence of compensation and work motivation on employee productivity at PT Amarilys Royal Tama.